Gut and skin microbial profiling of healthy and dropsy diseased Malaysian Mahseer Empurau (Tor tambroides) following exposure to antimicrobial agents - Chung, Hung Hui; Cindy Kho, Jia Yung; Fadlhlin Sakina, Zaidi; Fong, Jia Khi; Melinda Lau, Mei Lin; Leonard Lim, Whye Kit (Malaysian Society for Microbiology, 2025)
Aims: The study was aimed to identify bacterial pathogens from dropsy diseased Tor tambroides, compare the isolated bacteria from dropsy and healthy Empurau and assess their sensitivity towards various antibiotics. Methodology and results: To identify the possible causative agents of dropsy in diseased fish, we conducted pure culture of bacteria using spread plate techniques, Gram’s staining, KOH string test, 16S rRNA gene sequencing and antibiotics susceptibility test. Plate and microscopic observation revealed that most bacterial strains from healthy and dropsy diseased Empurau are Gram-negative, KOH reaction-positive and rod-shaped. The characterization of 16S rDNA sequence revealed that most of the bacteria were Pseudomonas spp., with a higher number identified in dropsy-affected Empurau than healthy ones. It is postulated that P. fluorescens, Aeromonas spp., Citrobacter freundii and P. congelans are the major causative agents of dropsy disease in Empurau fishes, but further investigations are required to strengthen this claim. Antibiotic susceptibility tests uncovered two multi-drug resistant bacterial strains (resistant to at least three antibiotics) from the gut and skin of healthy Empurau fish, respectively. Interestingly, all dropsy diseased Empurau gut isolates were susceptible to Morepenem and Tetracyclin, whereas all dropsy diseased Empurau skin isolates were susceptible to Chloramphenicol. Conclusion, significance and impact of study: The data on the possible causative agents of dropsy disease in Empurau fishes will be beneficial in managing fish bacterial diseases. The local aquaculture yield can be further improved through future research and elucidation on the biochemical characterization and disease management of bred Empurau fish.